Effects of kelp meal (Laminaria japonica) on the growth, nutrition, and intestinal health of the largemouth bass (Micropterus salmoides) - Qing Kong; Zixin Yang; Qiuwen Su; Jiafa Yang; Guohong Xiao; Dan Liu; Huijuan Tang (Aquaculture Reports)
Macroalgae are both highly productive and rich in bioactive molecules that have been shown to enhance growth and health of fish. Feed with high starch levels affects the health of fish. This study was conducted to investigate the effects of replacing partial starch with kelp (Laminaria japonica) meal (KM) on the growth performance, nutrient composition, and intestinal microbiota of largemouth bass (Micropterus salmoides, LMB). LMB (initial weight 13.00 ± 0.02 g) were fed three diets containing 0 % (K0), 5 % (K5), and 9 % (K9) kelp meal for 8 weeks. The results showed that with the addition of KM, growth performance and feed intake increased significantly, while hepatosomatic index decreased significantly. The whole body and muscle crude protein contents were significantly increased with the addition of KM. Liver catalase activity was significantly increased in K9, while serum malondialdehyde levels declined accordingly. Serum triglyceride, aspartate aminotransferase and alanine aminotransferase levels were significantly lower in K5 than in K0, suggesting that the addition of KM contributed to healthy liver function. The addition of KM to the diet significantly improved intestinal histology and amylase activity. In addition, the Chao index of the intestinal microbiome in the K5 group was significantly higher than in the K0 group. The relevant abundance of beneficial bacteria (Cetobacterium) tended to increase and that of pathogenic bacteria (Plesiomonas) tended to decrease with the addition of KM. In conclusion, partial replacement of starch with kelp meal increased growth performance, feed intake, muscle protein content, the antioxidant capacity and improved intestinal structure, as well as healthy intestinal microbiome. Kelp meal may be a beneficial substitute for starch for healthy aquaculture of M. salmoides.